POSSIBLE BREAKING POINTS IN SOCIETY’S DEVELOPMENT AND WAYS TO INFLUENCE THEM, OR PREVENTING AND OVERCOMING OF ECONOMIC RISKS IN THE PROCESS OF REALIZING OF THE STRATEGIC IMPERATIVES OF HUMANITY - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2024)
Among the strategic imperatives of humanity is the preservation and improvement of the ecumene. The creation of reliable resource and methodological bases for security and development is included in the list of humankind’s goals.